Food security and food sources linked to dietary diversity in rural smallholder farming households in Central Uganda - Nabuuma, Deborah; Ekesa, Beatrice; Faber, Mieke; Mbhenyane, Xikombiso (American Institute of Mathematical Sciences, 2021)
Undernourishment, low food quantity and poor dietary quality are common among smallholders in rural communities. A cross-sectional study of rural smallholder farming households (n=174) with children under five in Kiboga district, Uganda. Limited diversity of crops grown, low consumption of micronutrient-rich foods, child stunting, and household food insecurity were observed. Households had adequate food supply for 7.6±0.2 months a year and only 35% were food secure. Four household typologies 1st (29% households) and 2nd (23%) had more food secure households, 3rd (28%) had mild food insecurity and 4th (20%) had severe food insecurity. The 3rd and 4th typologies had the lowest dietary diversity. The household typologies can be used to develop context specific strategies to improve dietary diversity.